SISTEM AKUISISI DATA MULTIKANAL BERBASIS MIKROKONTROLLER ATMEGA8535 DENGAN TAMPILAN PADA PC - Irdawati - - (Saintia Fisika, 2013)
Has designed multichannel data acquisition system based microcontroller ATmega8535 with the display on the PC. Designed with multiple input channels, namely gas sensor, temperature sensor, light sensor and keypad as the input and the output used LCD and fan. As well as showing the results of the output to the PC. This tool is controlled by a microcontroller ATmega8535 which aims to process data generated by the sensor output in the form of voltage (analog data) are converted to digital data. The data from the microcontroller will appear to the PC as the display output through the serial communication is supported using visual basic program. In this study only simulates the temperature sensor and light sensor. So the PC will display the value of temperature and light conditions around the sensor (dark/light). If the value of temperature ≥50°C then the fan will be active, and if the value of temperature is < 50°C then the fan is off. Keywords: temperature sensor, light sensor, fan, microcontroller ATmega8535